Acquired hyperpigmentations - Tania Ferreira Cestari; Lia Pinheiro Dantas; Juliana Catucci Boza (Sociedade Brasileira de Dermatologia, 2014)
Cutaneous hyperpigmentations are frequent complaints, motivating around 8.5% of all dermatological consultations in our country. They can be congenital, with different patterns of inheritance, or acquired in consequence of skin problems, systemic diseases or secondary to environmental factors. The vast majority of them are linked to alterations on the pigment melanin, induced by different mechanisms. This review will focus on the major acquired hyperpigmentations associated with increased melanin, reviewing their mechanisms of action and possible preventive measures. Particularly prominent aspects of diagnosis and therapy will be emphasized, with focus on melasma, post-inflammatory hyperpigmentation, periorbital pigmentation, dermatosis papulosa nigra, phytophotodermatoses, flagellate dermatosis, erythema dyschromicum perstans, cervical poikiloderma (Poikiloderma of Civatte), acanthosis nigricans, cutaneous amyloidosis and reticulated confluent dermatitis